Integrating Citizen Science with Online Biological Collections to Promote Species and Biodiversity Literacy in an Entomology Course. (1st December 2021) - Paradise, Christopher; Bartkovich, Louisa
The integration of citizen science into undergraduate STEM courses improves science practice skills, enables students to contribute to the global collection of species occurrence data, and may increase understanding and appreciation of biodiversity. We integrated citizen science with a traditional insect collection in an entomology course at a liberal arts college. The activity targeted improvement of species and biodiversity literacy skills using online biological collections and identification resources. The citizen science component required students to upload images of insects to an online resource (BugGuide). We used formative and summative assessments, as well as a survey of students' experiences and perceptions to determine effectiveness. Formative assessments were useful in developing appreciation of citizen science and insect identification skills, whereas summative assessments revealed variable levels of achievement of species and biodiversity literacy. Students reported that the resources were useful in identifying specimens and learning about biodiversity, but some did not feel they were contributing as citizen scientists. They expected to earn a higher grade on their collection than they did; the lower-than-expected grades were mostly due to errors in identification and curation. The assignment and assessments can be easily modified for any course that includes examination of biodiversity and a citizen science component, including introductory biology, non-STEM-major diversity courses, and upper-level zoology or botany. Our semester-long approach to integrating biodiversity content and concepts with citizen science and online biological collections promotes species and biodiversity literacy.